COMPETENCE APPROACH IN PEDAGOGICAL STUDIES OF HIGHER EDUCATIONAL INSTITUTION: PROBLEMS OF SLEEPMENT (Pedagogy of Higher and Secondary Education, 2022)
The article contains the analysis of the experience implementations of competency point of view education practice of higher educational institution. Causes of make more active of the scientific-pedagogics community based through would realize of this innovation as a component of a change of the knowledge digm of sdudies.
Keywords: competence the approach; tool the competence